การพัฒนาแบบจำลองของเครื่องปฏิกรณ์ชีวเคมีแบบไร้อากาศ สำหรับผลิตแก๊สชีวมวลจากน้ำทิ้งโรงงานสกัดน้ำมันปาล์มดิบ - สิรีพร คชพันธุ์สุนทร (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The mathematical model was developed for simulation of a single anaerobic biochemical reactor operated at steady state with agitation, which provided uniform mixing. The developed model was separated into two parts, namely, start-up a culturing step and steadily operated step. Production of Volatile fatty acid and methane in each step was taken into account for predicting the reactor behavior. ISIM Simulation program was employed as tools to find out the solution of the mathematical model equations developed. Then the calculation results were compared with the actual data taken from the actually operating plant to find out the appropriate values of parameters of the model. It was found that after adjusting value of necessary parameters, the model could provide the results, which agreed with actual measurement results, especially for the start-up step. However, for the steadily operation step, it was found that the model could predict only the concentration of Volatile Fatty acid and substrate which agree with actual measurement results.